2008
DOI: 10.1074/jbc.m805823200
|View full text |Cite
|
Sign up to set email alerts
|

NblA, a Key Protein of Phycobilisome Degradation, Interacts with ClpC, a HSP100 Chaperone Partner of a Cyanobacterial Clp Protease

Abstract: When cyanobacteria are starved for nitrogen, expression of the NblA protein increases and thereby induces proteolytic degradation of phycobilisomes, light-harvesting complexes of pigmented proteins. Phycobilisome degradation leads to a color change of the cells from blue-green to yellow-green, referred to as bleaching or chlorosis. As reported previously, NblA binds via a conserved region at its C terminus to the ␣-subunits of phycobiliproteins, the main components of phycobilisomes. We demonstrate here that a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
90
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 80 publications
(95 citation statements)
references
References 73 publications
(65 reference statements)
2
90
0
Order By: Relevance
“…Binding experiments have shown that NblA interacts with the ␣-subunits of phycobiliproteins (18,19). In pull-down experiments, NblA was found to bind to ClpC, an HSP100 chaperone partner of a Clp protease, in an ATP-dependent manner (20). This result led to a proposed model of PBS degradation in which NblA acts as a so-called adaptor protein of a Clp protease (20).…”
mentioning
confidence: 94%
See 2 more Smart Citations
“…Binding experiments have shown that NblA interacts with the ␣-subunits of phycobiliproteins (18,19). In pull-down experiments, NblA was found to bind to ClpC, an HSP100 chaperone partner of a Clp protease, in an ATP-dependent manner (20). This result led to a proposed model of PBS degradation in which NblA acts as a so-called adaptor protein of a Clp protease (20).…”
mentioning
confidence: 94%
“…In pull-down experiments, NblA was found to bind to ClpC, an HSP100 chaperone partner of a Clp protease, in an ATP-dependent manner (20). This result led to a proposed model of PBS degradation in which NblA acts as a so-called adaptor protein of a Clp protease (20). Clp degradation complexes consist of two functional elements: a cylinder-like proteolytic core of two heptameric rings and an AAAϩ chaperone (21,22).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Last, the signaling pathway may include some adaptor proteins of proteases that recognize and bind both the substrates for degradation and the chaperone subunit of the protease (reviewed in Kirstein et al, 2009). For instance, in cyanobacteria, the NblA adaptor mediates the proteolytic degradation of phycobilisomes during nitrogen or sulfur starvation because of its double affinity for phycobilisome rods and for ClpC (Collier and Grossman, 1994;Karradt et al, 2008).…”
Section: Intracellular Nitrite Is the Most Likely Source Of No Producmentioning
confidence: 99%
“…Gram-positive bacteria such as S. aureus or B. subtilis do not encode homologues of SspB, although they contain ClpX. However, several adaptor proteins for ClpC have SsrA-tagged proteins in streptococci been identified in Gram-positive bacteria, including MecA, McsB, NblA, YpbH and TrfA (Andersson et al, 2006;Donegan et al, 2014;Karradt et al, 2008;Kirstein et al, 2007;Persuh et al, 2002;Turgay et al, 1998). All known ClpC activities require the participation of an adaptor protein (Kirstein et al, 2007(Kirstein et al, , 2009Schlothauer et al, 2003;Turgay et al, 1998;Wang et al, 2011).…”
Section: Discussionmentioning
confidence: 99%